Tinjauan Yuridis Pertanggungjawaban Hukum Marketplace Online terhadap Pelanggaran Hak Cipta - Alfis Setyawan; Kiki Ristanto (Journal of Judicial Review, 2016)
Online Marketplace has a strategic role in the surveillance, prevention and eradication of copyright infringement in its platform. If online marketplace does not take any necessary action, it is certain that the level of copyright infringement will increase along with the growth of national e-commerce industry. Considering the fact as stated above, author is interested in studying the legal liability of online marketplace regarding to copyright infringement, especially in the sale of pirated computer programs in pursuant to Indonesia Copyright Act. This study is using normative legal research study by applying the descriptive-qualitative method. Secondary data is applied in this study. Secondarydata is collected using the library research. Once all files have been collected, it will be processed and analyzed qualitatively, which means to compartmentalize the data based on studied aspects and described descriptively on the end. Results of this study showed that in terms of Law Number 28 of 2014 on Copyright, online marketplace is legally liable in criminal sentence in pursuant to article 114 of this copyright act and civil liability in term to article 10, breaching of article 10 is a tort of online marketplace. Furthermore, copyright owner is entitled the right to file a criminal report to police department or file a civil lawsuit through Indonesia commercial court, alternative dispute resolution and arbitration court against the copyright infringement. Few measures can be implemented by online marketplace to combat copyright infringement, included enjoinment and removal of infringing content and implementing word filter feature in the platform